The molecular genetic analysis of chromosomal DNA in burned bones - Zemskova, E Yu; Bordyukov, M M; Narina, N V; Kovalev, A V; Ivanov, P L (Sudebno-meditsinskaia ekspertiza, 2016)
The objective of the present study was a demonstrative consideration of the debatable problem concerning the possibility of obtaining reliable genetic information by the investigation of burned bones. The bone fragments with the identifiable external features of different degree of ignition (i.e. in the carbonized, grey- and white-burnt states) were placed in the muffle furnace for the controlled thermal treatment. The analytical suitability of these burned bone objects for genotyping was estimated with the use of standard chromosomal STR-loci multiplex genotyping panels. The results of the study cast serious doubts as regards the possibility of genotyping of chromosomal DNA extracted from the burned bones. It was shown that the exposure of the bone tissue to a temperature of 150 degrees Celsius during 2 hours can turn it into a material absolutely unsuitable for genotyping due to the loss of all individual genotypic traits. Characteristically the burned bone objects are externally indistinguishable from the native bone. At the same time, the material with the signs of the high-temperature impact visible by the unaided eye (e.g. in the carbonized, pronounced black as well as grey and white-burnt states) is altogether unsuitable for the reliable identification of the genetic profile of chromosomal DNA.